Translating brain research into educational practice - Wolfe, Pat; Fifth International Teaching for Intelligence Conference (Washington : SkyLight Professional Development, 1999)
Pat Wolfe discusses how teachers can use brain research to analyze the learning styles of students and better meet their needs
Executive producer, Ela Aktay
Keywords: Learning; Brain; Memory